2020
DOI: 10.1002/2211-5463.12862
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic acid supplementation ameliorates symptoms of diabetic kidney disease in mice

Abstract: Diabetic kidney disease (DKD) is among the most common and serious complications of both type 1 and type 2 diabetes. In this study, we used KK/Ta‐Ins2Akita (KK‐Akita) mice as a model of DKD and KK/Ta (KK) mice as controls to identify novel factors related to the development/progression of DKD. Capillary electrophoresis coupled with mass spectrometry analysis revealed that circulating Asp (l‐aspartic acid) levels in diabetic KK‐Akita mice tend to be lower than those in control KK mice. Therefore, we evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
12
1
Order By: Relevance
“…In the present study, Asp was the most abundant amino acid identified in all samples, ranging from 28.10 to 63.57 mg/100 g. Recently, it has been shown that Asp could be successfully used in the prevention of diabetic kidney mice disease, highlighting the importance of this non-essential amino acid in kidney oxidative stress reduction [ 50 ]. Asp was identified in high amounts also by Zhang et al [ 51 ] at the maturity stage of Honeycrisp apples, but also as the second most abundant amino acid in apple Malus domestica Borkh cv.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the present study, Asp was the most abundant amino acid identified in all samples, ranging from 28.10 to 63.57 mg/100 g. Recently, it has been shown that Asp could be successfully used in the prevention of diabetic kidney mice disease, highlighting the importance of this non-essential amino acid in kidney oxidative stress reduction [ 50 ]. Asp was identified in high amounts also by Zhang et al [ 51 ] at the maturity stage of Honeycrisp apples, but also as the second most abundant amino acid in apple Malus domestica Borkh cv.…”
Section: Discussionmentioning
confidence: 61%
“…The color characteristics of the final biscuits were analyzed according to our recent work [ 50 ], by using an NH 300 portable colorimeter (Shenzhen ThreeNH Technology Co., Ltd., Shenzhen, China), having a color system based on CIE L* (luminosity), a* (red/green coordinate), b* (yellow/blue coordinate) color. The colorimeter was previously calibrated using its own black and white calibration system.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a study demonstrated that L-aspartate supplementation could ameliorate diabetic kidney disease in mice. 47 In mechanism, a latest study done by Jiang et al revealed that L-aspartate can directly interact with phosphorylated LKB1 leading to an activation of LKB1-AMPK axis in cells. 37 Consistently, our study also found L-aspartate treatment activated LKB1-AMPK axis in hepatocyte and intestinal cells, enhanced lipid oxidation and inhibited oxidative stress and its induced cell injury, thus ameliorating MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…L-aspartate is a non-essential amino acid and involved in treatment for acute and chronic liver hepatitis and cirrhosis treatment in the clinic by regulating nitrogen metabolism, nucleic acid synthesis and the Kreb's cycle (Hou et al, 2017;Leng et al, 2014). Recently, a study reported that L-aspartate supplementation ameliorated diabetic kidney disease in mice (Ichikawa et al, 2020). Moreover, Jiang et al revealed that L-aspartate directly interacted with phosphorylated LKB1 and activated the LKB1-AMPK axis in cells (Deng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%